PRE-INCUBATION FRAMEWORK OF SOFTWARE STARTUP USING GROW COACHING MODEL, BLOCK SCHEDULING AND DAILY SCRUM - Eko Heri Susanto (Department of Computer Engineering, Universitas Wiralodra, 2022)
Pre-incubation of software startup is a training and coaching activity to improve understanding of knowledge and skills in developing software. The problem that occurs between education in universities and business incubators is the gap, namely the lack of mastery of knowledge and skills in developing software. The solution to this problem is to develop a framework for pre-incubation activities. In this framework, the methodology is used as a combination of the GROW coaching model, block scheduling, and daily stand-up meeting (daily scrum). If before participating in the pre-incubation the tenant takes 4 months to 6 months to build a website application, then after participating in the pre-incubation the tenant can create a website application within 1 week to 4 weeks.